Application of local gene induction by infrared laser‐mediated microscope and temperature stimulator to amphibian regeneration study. (29th October 2015) - Kawasumi‐Kita, Aiko; Hayashi, Toshinori; Kobayashi, Takuya; Nagayama, Chikashi; Hayashi, Shinichi; Kamei, Yasuhiro; Morishita, Yoshihiro; Takeuchi, Takashi; Tamura, Koji; Yokoyama, Hitoshi
Abstract : Urodele amphibians (newts and salamanders) and anuran amphibians (frogs) are excellent research models to reveal mechanisms of three‐dimensional organ regeneration since they have exceptionally high regenerative capacity among tetrapods. However, the difficulty in manipulating gene expression in cells in a spatially restricted manner has so far hindered elucidation of the molecular mechanisms of organ regeneration in amphibians. Recently, local heat shock by laser irradiation has enabled local gene induction even at the single‐cell level in teleost fishes, nematodes, fruit flies and plants. In this study, local heat shock was made with infrared laser irradiation (IR‐LEGO) by using a gene expression inducible system in transgenic animals containing a heat shock promoter, and gene expression was successfully induced only in the target region of two amphibian species, Xenopus laevis and Pleurodeles waltl (a newt), at postembryonic stages. Furthermore, we induced spatially restricted but wider gene expression in Xenopus laevis tadpoles and froglets by applying local heat shock by a temperature‐controlled metal probe (temperature stimulator). The local gene manipulation systems, the IR‐LEGO and the temperature stimulator, enable us to do a rigorous cell lineage trace with the combination of the Cre‐LoxP system as well as to analyze gene function in a target region or cells with less off‐target effects in the study of amphibian regeneration. Abstract : A local heat shock by infrared laser irradiation (IR‐LEGO) is applicable to amphibians to induce gene expression only at the target cells. A local heat shock by a temperature‐controlled metal probe (temperature stimulator) is also applicable to an amphibian to induce wider gene expression at the target tissue. These techniques enable us to do a rigorous cell lineage trace as well as to analyze gene function in a target region or cells in study of amphibian regeneration.